Tes Sebagai Alat ukur Prestasi Akademik - Suharman Suharman (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
Teaching and learning process carried out must always go through the final process of evaluation, so that the results to be achieved are better. One of evaluation technique that is often used by educational institutions is achievement tests. Achievement tests are tests that are arranged in a planned manner to reveal the subject’s maximum performance in mastering the material or material that has been taught. In compiling test instruments for achievement tests, the test instrument must go through the Validity and Reliability Test. So the, test that will be prepared can be commensurate with the ability of someone who will be given a test. The test instruments that are prepared should not be too far below or above the ability of the test participants, and the level of difficulty of the items should be in the medium category. In the study of the test there are two approaches that can be used, namely the classical approach (CTT) and the modern approach based on Item Response Theory (IRT)